Cancer stem cell mediated acquired chemoresistance in head and neck cancer can be abrogated by aldehyde dehydrogenase 1 A1 inhibition. Issue 2 (4th August 2016) - Kulsum, Safeena; Sudheendra, Holalugunda Vittalamurthy; Pandian, Ramanan; Ravindra, Doddathimmasandra Ramanjanappa; Siddappa, Gangotri; R, Nisheena; Chevour, Priyanka; Ramachandran, Balaji; Sagar, Milind; Jayaprakash, Aravindakshan; Mehta, Alka; Kekatpure, Vikram; et al.
Abstract : Chemoresistance leading to disease relapse is one of the major challenges to improve outcome in head and neck cancers. Cancer Stem Cells (CSCs) are increasingly being implicated in chemotherapy resistance, this study investigates the correlation between CSC behavior and acquired drug resistance in in vitro cell line models. Cell lines resistant to Cisplatin (Cal‐27 CisR, Hep‐2 CisR) and 5FU (Cal‐27 5FUR) with high Resistance Indices (RI) were generated (RI ≥ 3) by short‐term treatment of head and neck squamous cell carcinoma (HNSCC) cell lines with chemotherapeutic drugs (Cisplatin, Docetaxel, 5FU), using a dose‐incremental strategy. The cell lines (Cal‐27 DoxR, Hep‐2 DoxR, Hep‐2 5FUR) that showed low RI, nevertheless had a high cross resistance to Cisplatin/5FU ( P < 0.05). Cal‐27 CisR and DoxR showed 12–14% enrichment of CD44+ cells, while CisR/5FUR showed 4–6% increase in ALDH1A1+ cells as compared to parental cells ( P < 0.05). Increased expression of stem cell markers (CD44, CD133, NOTCH1, ALDH1A1, OCT4, SOX2) in these cell lines, correlated with enhanced spheroid/colony formation, migratory potential, and increased in vivo tumor burden ( P < 0.05). Inhibition of ALDH1A1 in Cal‐27 CisR led to down regulation of the CSC markers, reduction in migratory, self‐renewal and tumorigenic potential ( P < 0.05) accompanied by an induction of sensitivity to Cisplatin ( P < 0.05). Further, ex vivo treatment of explants ( n = 4) from HNSCC patients with the inhibitor (NCT‐501) in combination with Cisplatin showed a significant decrease in proliferating cells as compared to individual treatment ( P = 0.001). This study hence suggests an ALDH1A1‐driven, CSC‐mediated mechanism in acquired drug resistance of HNSCC, which may have therapeutic implications. © 2016 Wiley Periodicals, Inc.